Quality Control Analysis of Cover Flange Products with Six Sigma Approach at PT. SMI - Tri Nurhasanah, Anggita Nafiulana; Restuasih, Sinta; Haryudiniarti, Ayu Nurul (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
PT. SMI is a manufacturing company engaged in manufacturing services specializing in heavy equipment components. In the production process activities there are still several factors that cause a product that has been produced not in accordance with predetermined specifications. Therefore, this study aims to determine the types and factors that can cause deffects and provide proposals for improving the Cover Flange at PT. SMI. The method used is the Six Sigma DMAIC method (Define, Measure, Analyze, Improve, Control) which is quality control to minimize the number of defective products. Based on the results of data processing analysis, there are still data that are still outside the control limits. Therefore, the production process still has to be improved in order to improve quality. The DPMO (Defect Per Million Opportunities) value before improvement is 106456 and the sigma value is 2.70. The proposed improvement used in this study is to use the 5S method (Seiri, Seiton, Seiso, Seikersu, Shitshuke) So, the results obtained after applying the 5S method are a reduction in the DPMO value of 51579 and a sigma value of 3.15 with a reduction in the number of defective Cover Flange products, so with the improvement being able to provide changes in the DPMO value and sigma value of PT. SMI.